POTENSI EKSTRAK N-HEKSANA, DIKLOROMETANA, ETILASETAT JAMUR DEWA (Agaricus blazei Murill) TERHADAP Escherrichia coli DAN Staphylococcus aureus - Misgiati Misgiati (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2022)
Dewa mushroom is a saprophytic mushroom that can function as medicine, namely antihypertensive, antibacterial, anticancer, immunostimulant, anticholesterol, antiviral, and antioxidant. The content of secondary metabolites of terpenoids, alkaloids, phenols have antibacterial activity. The extract was obtained by stepwise extraction with hexane, dichloromethane, and ethylacetate as solvents. Testing of antibacterial activity by diffusion method. The results obtained that hexane extract, dichloromethane extract, and ethylacetate extract had inhibitory power against Escherrichia coli and Staphylococcus aureus. There were significant differences in the three extracts against Escherrichia coli. Whereas in Staphylococcus aureus there was a significant difference between dichloromethane extract and ethylacetate extract, and for hexane extract to dichloromethane extract and ethyl acetate extract there was no significant difference (having the same inhibitory power)